The Difference in School Well-Being in High School Students with Full-Day Scholl and Half Day School Systems - Rahma, Ulifa; Pramitadewi, Rr. Karina Putri; Saribu, Risna Hotmauli Tambun; Faizah, Faizah; Perwiradara, Yuliezar (Psikopedagogia, 2019)
This study aims to determine the differences in the school well-being of the full-day school and half-day high school students. The method used in this research is a quantitative correlational method with a population of 249 full day school students and 304 half-day schools with a total of 552. Sampling using accidental sampling The instrument in this study, namely, the school well-being profile questionnaire ( SWP), is based on Konu and Rimpela's theory, where there are four dimensions (having, loving, being, health). The results showed that there was no difference in school well-being among high school students with full-day school and half-day school systems. The results of the study are useful as a basis for providing guidance and counseling service techniques to improve school well-being in students.